Turning Agricultural Biomass Ash into a Valuable Resource in the Construction Industry—Exploring the Potential of Industrial Symbiosis - Olivera Bedov; Ana Andabaka; Suzana Draganić (Buildings)
This paper presents a circular business model (CBM) designed to promote the valorization of agricultural biomass ash for producing an alternative binder in construction, aiming to reduce CO₂ emissions and landfill waste. The circular economy framework emphasizes regeneration and restoration to minimize resource and energy use, waste generation, pollution, and other environmental impacts. Aligned with these principles of sustainability, the construction industry, energy sector and food processing industry can establish a shared interest through industrial symbiosis. In the proposed CBM, waste from one industry becomes an input for another. The model leverages industrial symbiosis by using sunflower husk ash (SHA) as an alternative hydroxide activator for alkali-activated materials. A case study of companies in the Republic of Serbia that produce SHA as waste forms the basis for this model, featuring promising results of experimental testing of three alkali-activated mortars produced by activating ground-granulated blast furnace slag (GGBFS) with different SHA contents (15, 25 and 35 wt% GGBFS), instead of commercially available hydroxide activators. The potential of SHA as an alternative activator was assessed by testing flow diameter and compressive strength at 7 and 28 days of curing. The highest 28-day compressive strength was attained for the addition of 25% SHA (28.44 MPa). The promising results provided a valid basis for CBM development. The proposed CBM is stream-based, resulting from merging and upgrading two existing industrial symbioses. This study highlights the benefits of the CBM while addressing the challenges and barriers to its implementation, offering insights into the possible integration of agricultural biomass ash into sustainable construction practices.